Processes Underlying the Year‐To‐Year Fluctuations of the Global Mean Surface Temperature - Angela Jiang; Jonathan H. Jiang; Bin Guan (Atmospheric Science Letters)
ABSTRACT In addition to the global mean surface temperature (GMST), accurately predicting regional features associated with GMST changes is essential for effective climate policymaking at the regional level. This study investigates regional patterns of surface temperature and precipitation associated with interannual GMST variability and evaluates their representation in state‐of‐the‐art climate models. Although the influence of the El Niño‐Southern Oscillation (ENSO) on GMST variability is well recognized, it accounts for less than 50% of the total interannual variability. A significant portion of GMST warming, independent of ENSO, is closely associated with widespread regional warming—most notably over North America—along with increased atmospheric river activity and enhanced precipitation along its west coast. However, current climate models systematically underestimate the ENSO‐independent component of GMST variability, thereby introducing uncertainties into our interpretation of GMST changes.